4-Hydroxydibenzyl: a novel metabolite from the human gut microbiota after consuming resveratrol. Issue 14 (28th June 2022) - Iglesias-Aguirre, C. E.; Vallejo, F.; Beltrán, D.; Berná, J.; Puigcerver, J.; Alajarín, M.; Selma, M. V.; Espín, J. C.
Abstract : 4-Hydroxydibenzyl is a novel metabolite produced by the human gut microbiota from resveratrol after sequential dehydroxylations at the 5- and 3-positions. Abstract : Resveratrol (RSV) was known to be metabolised by the gut microbiota to dihydroresveratrol, lunularin (LUNU), and (or) 3, 4′-dihydroxy- trans -stilbene (DHST). We describe here for the first time that LUNU can be further dehydroxylated, but only at the 3-position, to yield 4-hydroxydibenzyl, a novel metabolite found in human urine after RSV intake in 41 out of 59 healthy participants. In contrast, DHST was not further dehydroxylated, and thus, 4-hydroxy- trans -stilbene was not detected as a gut microbial metabolite of RSV. Faecal in vitro incubations confirmed the in vivo results.